Validitas Kepastian Hukum Kontrak Elektronik dan Kontrak Manual - Moh.Alfan Baetoni; Lucky Dafira Nugroho; Hudama Leo Putra Perkasa (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
The development of information technology has driven significant changes in the practice of contract making, from manual-based to increasingly using electronic systems. This research discusses the validity of the legal certainty of electronic contracts compared to manual contracts. Electronic contracts offer efficiency and flexibility, but raise concerns regarding the validity of electronic signatures, data security, and legal proof in the event of a dispute. Meanwhile, manual contracts are considered more concrete and easily accepted as evidence due to their physical form. Through a normative approach with the analysis of laws and regulations and legal literature, this study found that both types of contracts have equal legal standing as long as they fulfill the legal requirements of an agreement according to the Civil Code. However, electronic contracts face challenges in legal protection, identity authentication, and document integrity. It is necessary to strengthen technical regulations, digital legal education, and technological infrastructure to ensure the validity and legal certainty of electronic contracts to be equivalent to manual contracts, so that the rights and obligations of the parties can be fairly protected in today's digital era.